2019
DOI: 10.1155/2019/3548917
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Potential of Wharton’s Jelly Mesenchymal Stem/Stromal Cells

Abstract: The benefits attributed to mesenchymal stem/stromal cells (MSC) in cell therapy applications are mainly attributed to the secretion of factors, which exhibit immunomodulatory and anti-inflammatory effects and stimulate angiogenesis. Despite the desirable features such as high proliferation levels, multipotency, and immune response regulation, there are important variables that must be considered. Although presenting similar morphological aspects, MSC collected from different tissues can form heterogeneous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 79 publications
(83 reference statements)
1
28
0
Order By: Relevance
“…LG polypeptides stimulated UC -MSCs to reduce the release of a pro-inflammatory factor instability of the internal environment, and increase UC-MSCs immune regulation and regenerative biology, which conformed to the principle of the main pathogenesis of TCM. [ 23 , 30 ] This study showed that the improvement of HAQ, DAS28, ESR, CRP, RF, and Anti-CCP in the LG + UC -MSC group was significantly better than that in the UC -MSC group at 1 year after treatment (P < 0.05), and all patients conformed the ACR20 standard. This indicated that TCM intervention played an important role in anti-inflammation, regulating immunity and improving microcirculation in the treatment of UC-MSCs, which was beneficial to the migration of UC-MSCs and repair of damaged tissue.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…LG polypeptides stimulated UC -MSCs to reduce the release of a pro-inflammatory factor instability of the internal environment, and increase UC-MSCs immune regulation and regenerative biology, which conformed to the principle of the main pathogenesis of TCM. [ 23 , 30 ] This study showed that the improvement of HAQ, DAS28, ESR, CRP, RF, and Anti-CCP in the LG + UC -MSC group was significantly better than that in the UC -MSC group at 1 year after treatment (P < 0.05), and all patients conformed the ACR20 standard. This indicated that TCM intervention played an important role in anti-inflammation, regulating immunity and improving microcirculation in the treatment of UC-MSCs, which was beneficial to the migration of UC-MSCs and repair of damaged tissue.…”
Section: Discussionmentioning
confidence: 77%
“…Through the latter, MSC can regulate the immune response mediated by T cells, inhibit the production and function of various innate immune cells and play an anti-inflammatory role, regulate immunity and resist tissue injury. [ 23 ] Our previous study [ 18 ] has shown that UC- MSCs therapy for RA can reduce and alleviate the clinical symptoms of RA, and there is no significant change in human blood routine indicators, which showed good safety.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the signals sensed by MSCs, they can migrate and home within a specific tissue. Indeed, MSCs are sensitive to shifts in the local milieu as they harbor a panel of receptors activating various signaling pathways (Paladino et al, 2019). We have previously shown that MSCs express several relevant receptors, such as the receptor for advanced glycation endproducts (RAGE), C-type lectin receptors (CLRs, including DECTIN-1, DECTIN-2 and MINCLE), leukotriene B4 (LTB4) receptors (BLT1 and BLT2) and cysteinyl leukotriene (CysLTs) receptors (CYSLTR1 and CYSLTR2) (Najar et al, 2018).…”
Section: Mscs Are Environmentally Responsivementioning
confidence: 99%
“…MSCs adopt a specific phenotype to suppress or promote immune responses depending on the inflammatory microenvironment in which they reside. Current studies on the immunomodulatory abilities of MSCs have focused on the interaction between MSCs and inflammatory monocytes [6,7]. Our previous studies have proven that a lower deployment of Ly6C high monocytes after AMI could improve the effectiveness of MSC transplantation and selectively ameliorate myocardial remodeling [8].…”
Section: Introductionmentioning
confidence: 99%
“…(b) Survival functions of C57BL/6 CX3CR1-/mice (red solid line) and C57BL/6 wild mice (blue dotted line) following MSC transplantation after AMI. Abbreviations: MSCs: mesenchymal stem cells 6. Stem Cells International…”
mentioning
confidence: 99%